MALDI imaging mass spectrometry of Pacific White Shrimp L. vannamei and identification of abdominal muscle proteins. Issue 11 (9th May 2016) - Schey, Kevin L.; Hachey, Amanda J.; Rose, Kristie L.; Grey, Angus C.
Abstract : MALDI imaging mass spectrometry (IMS) has been applied to whole animal tissue sections of Pacific White Shrimp, Litopenaeus vannamei, in an effort to identify and spatially localize proteins in specific organ systems. Frozen shrimp were sectioned along the ventral‐dorsal axis and methods were optimized for matrix application. In addition, tissue microextraction and homogenization was conducted followed by top‐down LC‐MS/MS analysis of intact proteins and searches of shrimp EST databases to identify imaged proteins. IMS images revealed organ system specific protein signals that highlighted the hepatopancreas, heart, nervous system, musculature, and cuticle. Top‐down proteomics identification of abdominal muscle proteins revealed the sequence of the most abundant muscle protein that has no sequence homology to known proteins. Additional identifications of abdominal muscle proteins included titin, troponin‐I, ubiquitin, as well as intact and multiple truncated forms of flightin; a protein known to function in high frequency contraction of insect wing muscles. The combined use of imaging mass spectrometry and top‐down proteomics allowed for identification of novel proteins from the sparsely populated shrimp protein databases.